Uncovering State Sharing Practices for Birth Method-of-Delivery Data in the United States [6K]. (May 2018) - Bradley, Danielle; Landau, Erin; Jesani, Noreen; Baron, Alex; Wolfberg, Adam
Abstract : INTRODUCTION: Enabling the work of practitioners and policy makers aiming to address the US cesarean epidemic requires publicly-available, reliable, hospital-level data for birth method-of-delivery to be made available. With hospital choice being a primary determinant of birth method-of-delivery, the need for quality data to inform patient decision-making and encourage provider behavior change has never been more pertinent. METHODS: Reporting of birth counts and delivery methods is mandated in the US. To collect quality metric data, the investigators searched state websites and contacted vital statistics departments. States and regions were scored based on "sharing" and "barrier" metrics. "Sharing" refers to level of data shared, while "barrier" refers to data collection limitations. RESULTS: Twenty-eight states offered hospital-level data. Others offered method-of-delivery data on a county-of-birth-occurrence-level (10), a county-of-mother's-residence-level (6), or did not provide data (6+D.C.). Of the 44 states that shared data, 12 required a signed data use form, which outlined stipulations and limitations for data use. The West achieved the best data availability scores, while the Midwest region ranked the poorest. CONCLUSION: Twenty-two states and D.C. failed to share hospital-level data for method-of-delivery. Of the 28 states that shared hospital-level data, a minimum of seven do not allow public sharing of their data. Selecting a hospital based on quality metric data would improve patient outcomes, reduce the national cesarean rate, and help control healthcare costs. Availability of method-of-delivery data was highly variable across the country, contributing to the lack of transparency in the US healthcare system.